Attitudes of subordinates toward women in leadership position (2008)
The study investigated how women in leadership position are perceived accepted and evaluated by their subordinates. In an attempt to elicit subjects' response, the subordinates attitude questionnaire scale was constructed and was administered to 222 workers consisting of 111 males and 111 females drawn from University of Ibadan, Oyo State Secretariat, Nigerian Bottling Company, National Bank of Nigeria, First Banks Nigeria, Chartered Bank, and Cooperative Bank. The t-test of independent sample was used to analyse the research data. The findings revealed that: (a) Male subordinates have negative attitude toward women leader; (b) Subordinates with higher educational qualification have positive attitude towards women leaders; (c) Young subordinates have negative attitudes toward women in leadership position; (d) Christian subordinates have positive attitude toward women in leadership positions than their Moslem counterparts